1999
DOI: 10.1016/s0370-2693(98)01477-4
|View full text |Cite
|
Sign up to set email alerts
|

Precision measurement of scaled momentum, charge multiplicity, and thrust in νμN and interactions

Abstract: We report the first precision measurements of the scaled momentum, the charge multiplicity, and the thrust of hadronic jets in the Breit frame in Deep Inelastic Scattering ν µ N andν µ N charged current events over the Q 2 range from 1 to 100 GeV 2 . The neutrino data, obtained in the NOMAD experiment at the CERN SPS, extend the Q 2 -evolution of these parameters by two orders of magnitude, and with commensurate precision, when compared to those reported by the ep and e + e − experiments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
9
0

Year Published

2001
2001
2015
2015

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 21 publications
1
9
0
Order By: Relevance
“…2. As it shown in [1] the NOMAD multiplicity values n ch are very close to < n ch > /2 results from e + e − experiment [11] at energy E = √ s and < n ch > from ep andν µ p at E = Q. In Fig.…”
supporting
confidence: 84%
See 3 more Smart Citations
“…2. As it shown in [1] the NOMAD multiplicity values n ch are very close to < n ch > /2 results from e + e − experiment [11] at energy E = √ s and < n ch > from ep andν µ p at E = Q. In Fig.…”
supporting
confidence: 84%
“…Such an analysis has been performed recently in Ref. [1]. It has also been found that a perturbative QCD calculation results in a good description of the charged hadron multiplicity < n ch > measured in e + e − annihilation and ep DIS at initial energies E = √ s = Q > 5 GeV/c [1], whereas a similar calculation of < n ch > in the current region of processes ν(ν) p → µ − (µ + ) h X cannot reproduce the NOMAD data at Q < 5 GeV/c .…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[40] in the current hemisphere of the Breit (or "brick wall") frame where the incoming quark scatters off the photon and returns along the same axis. In addition, we include also into our global fit the 55 direct measurements of FF moments (mostly multiplicity, peak, and width) from H1 [41] and ZEUS [42] experiments in e ± -p at HERA, and NOMAD (ν-N scattering) [43], covering the range of four-momentum transfers Q ≈ 1-180 GeV. The total final number of FF moments extracted from the DIS jet data is 160 and, thus, the combined global fit of e + e…”
Section: Extraction Of α Smentioning
confidence: 99%